Ambient Music Dalam Pembelajaran (Studi Eksperimen Terhadap Konsentrasi Dan Hasil Belajar Mahasiswa Pada Mata Kuliah Genetika) - Dharma Ferry (Symbiotic: Journal of Biological Education and Science, 2023)
The purpose of this research is to determine the influence of ambient music on the concentration levels and learning outcomes of students with an auditory learning style in the genetics course. This study is quasi experimental research using a monomethod Multistrand Design with sequential data collection. The first stage of data collection was conducted to obtain data on auditory learning styles in students, which were later divided into two groups (experimental and control). The sampling technique in this study was done randomly. Based on the Slovin formula, the research sample size was determined to be 77 participants for collecting learning style data. Subsequently, from the 77 participants, 26 students with an auditory learning style were identified. Data were collected using a learning style questionnaire, the Army Alpha Intelligence Test, and exams. Based on hypothesis testing using the t-test, the concentration level of student learning showed a Sig. (2-tailed) t-test value of 0.023, and the student learning outcomes showed a Sig. (2-tailed) t-test value of 0.035, both <0.05. The results of the study indicate that the provision of ambient music in learning can have a positive impact on the concentration levels and learning outcomes of students in the genetics course.